Detection of Cervical Lymphnode Metastasis in Oral Squamous Cell Carcinoma by Ultrasonogram Guided Fine Needle Aspiration Cytology (FNAC) and Comparison with Computed Tomographic (CT) Findings (KYAMC Journal, 2017)
Background: Several imaging methods are using for investigating the presence and extent of nodal metastasis including Computerized Tomography, Magnetic Resonance Imaging, Radionuclide scintigraphy, Positron Emission Tomography and Ultrasound Guided FNAC. To find out the over all accuracy of detection of metastatic lymph nodes by two available and cost effective methods (Ultrasound Guided FNAC and CT scan) will help to make an effective treatment protocol.Objectives: This study opted to compare the relative sensitivity and specificity of Ultrasound Guided FNAC and CT scan in the detection of lymph node metastasis in oral squamous cell carcinoma.Materials & Methods: 37 patients were included with oral squamous cell carcinoma and both Ultrasound Guided FNAC and CT scan were done in all these patients. Later, following surgical excision, histopathology reports of the patient's neck nodes were collected.Results: CT scan of the neck nodes revealed 26 of the subjects having nodal metastasis; there was 1 (2.7%) false positive node and 1 (2.7%) false negative nodes. Sensitivity of CT scan test was found 96.15 % and specificity was found 90.9%. Positive predictive value and negative predictive value was found 96.15% and 90.9% respectively, and the accuracy was found 94.59%, Ultrasound Guided FNAC detected 25 (67.6%) metastatic lymph node. Among those 1 (2.7%) was false positive and 2 (5.4%) were false negative. It showed 92.3% sensitivity and 90.9% specificity. Positive predictive value and negative predictive value of the test were 96.0% and 83.3% respectively and accuracy was 91.89%.Conclusion: Ultrasound Guided FNAC was found comparable to CT scan in the evaluation the node metastasis. Both the two tests showed high sensitivity, specificity and overall accuracy.KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 391-397